Theoretical examinations of optical tomography through scattering medium - Zhang, Fan (2015)
Optical tomography is considered to be a non-invasive and non-ionising technique that can create a digital volumetric model of an object by reconstructing 3D images made from light transmitted and scattered through the object. It is becoming of increasing importance in the area of tissue engineering and biomedical diagnostics. The main limit of pure optical techniques is the heavy scattering of tissue, which causes a poor imaging resolution. Ultrasound modulated optical tomography (USMOT) combines optical and ultrasonic techniques to produce optical contrast at ultrasound resolution. The modulation mechanism for incoherent USMOT is considered to be a secondary effect when coherent light is used. However, it is still valuable as it offers a chance to simulate the modulation of fluorescent light. In this thesis, several models of fluorescence imaging systems are presented including incoherent USMOT, Fluorescence lifetime extraction system, full field illumination (FI) system and scanning input (SI) system. A simple incoherent USMOT model is presented which allows varying of acoustic and optical parameters to provide an optimum setup to measure the incoherent USMOT effect. Afterwards, the combination of incoherent USMOT and fluorescence imaging is applied to provide an optimized SNR of modulated fluorescent light by changing the modulation frequency. With the presence of ultrasound, a novel lifetime extraction technique is presented which provides more accurate lifetime measurements and further makes it possible to extract fluorescence lifetimes in a heavily scattering medium. A broad range of excitation and emission optical parameters of NIR fluorescence imaging system have been investigated which aims to find out the optimized imaging pairs based on the SNR and spatial resolution detected. The scanning input system turns out to be better than the full field illumination system based on the spatial resolution detected, and longer wavelengths may lead to a higher SNR but degraded spatial resolution. The spatial resolution has been taken into account in fluorophore and imaging system selection over a broad range of excitation and emission wavelength. Experimental results are shown as well as a supplement to the simulations.